Novel super-hydrogel fiber cold storage material for cold chain and preparation method of novel super-hydrogel fiber cold storage material
Through the preparation of new superhydrogel fiber materials, the shortcomings of existing cooling materials in cooling capacity and temperature control are solved, high specific heat capacity and effective temperature control are achieved, and food safety and transportation efficiency are ensured.
Patent Information
- Application Number
- CN202411506523.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing cooling materials have insufficient cooling capacity, and it is difficult to effectively control the temperature in cold chain logistics, affecting food safety and transportation efficiency.
The new superhydrogel fiber material is prepared through polymer synthesis, hot melt blowing, alkaline hydrolysis and three-dimensional crosslinking, forming a superhydrogel fiber cooling material with high specific heat capacity.
It achieves higher specific heat capacity, can store and release more cold volume, provides more effective temperature control, enhances the structural stability and flexibility of the material, and ensures food safety and transportation efficiency.
Smart Images

Figure CN119531127A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cold storage materials, and in particular to a novel super hydrogel fiber cold storage material for cold chain and a preparation method thereof. Background Art
[0002] With the rise of the fresh food e-commerce industry, cold chain logistics has become increasingly important, and cold storage materials have been increasingly used. These materials play a role in controlling temperature, reducing energy consumption, and transferring energy loads in cold chain logistics. In areas such as cold chain logistics that require precise temperature control, cold storage materials with high specific heat capacity can more effectively maintain a constant low temperature environment and reduce the impact of external temperature fluctuations on goods.
[0003] At present, cold storage materials can be divided into two categories: organic and inorganic. Organic phase change materials include paraffin, fatty acids, esters and alcohols, which have the characteristics of excellent phase change enthalpy, low corrosiveness and good thermal stability, but have low thermal conductivity, flammability and high cost. Inorganic phase change materials such as ice and hydrated salts have the advantages of low cost and high thermal conductivity, but have disadvantages such as high supercooling, severe phase separation and strong corrosiveness. In addition, the above-mentioned cold storage materials also have certain deficiencies in cold storage capacity. The specific heat capacity of the above-mentioned materials is roughly about 120% to 200% of water. Summary of the invention
[0004] The purpose of the present invention is to provide a new super hydrogel fiber cold storage material for cold chain and a preparation method to solve the problems existing in the prior art. In order to achieve the above purpose, the technical solution of the present invention provides a new super hydrogel fiber cold storage material for cold chain and a preparation method.
[0005] The invention discloses a method for preparing a novel super hydrogel fiber cold storage material for cold chain, comprising the following steps: S1, polymer synthesis, placing acrylic acid monomers in a solvent for polymerization reaction to obtain a hot-melt acrylic ester polymer; S2, polymer hot-melt spinning, crushing the product obtained in step S1 and forming a fiber product through hot-melt high-pressure spinning; S3, alkaline hydrolysis, alkaline hydrolysis of the product obtained in step S2; S4, three-dimensional cross-linking, using a cross-linking mixed liquid to evenly spray the surface of the hydrophilic gel fiber obtained in step S3, the cross-linking mixed liquid comprising methanol, water, aziridine, ethylene glycol diglycidyl ether or glycerol triglycidyl ether.
[0006] Furthermore, the acrylic acid monomer in step S1 includes one or more combinations of acrylic acid and acrylic acid esters; the acrylic acid esters include methyl acrylate, butyl acrylate, ethyl acrylate, and propyl acrylate; the ratio of acrylic acid to acrylic acid ester monomers is 1:(3-5); and the solvent system of the polymerization reaction is any one of cyclohexane, xylene, and ethyl acetate.
[0007] Furthermore, the specific process of the polymerization reaction in step S1 is as follows: the acrylic acid monomer is mixed evenly with the initiator, the solvent is heated to 50-90°C in a water bath, and the monomer solution containing the initiator is slowly dripped into the reaction solvent, and the dripping time is 1-3 hours; stirring is performed during the dripping process, and the mass of the reaction monomer is controlled to be 25%-40% of the mass of the solvent. After the monomer is dripped, the reaction temperature is maintained for 3-5 hours; after the insulation is completed, the granular product is filtered and separated from the solvent to obtain a granular product, and the granular product is washed and dried to obtain a hot-melt acrylic ester polymer; the initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate, and the amount of the initiator is 1-5 ten-thousandths of the monomer mass.
[0008] Furthermore, the specific process of step S2 is as follows: the product obtained in step S1 is crushed into particles larger than 20 meshes, and a fiber product is formed by hot melt high pressure spinning. The hot melt spinning temperature is 180-250°C, the pressure is 0.8-2.5Mpa, and the ejected filamentous fibers are cooled and solidified by normal temperature water, and the fiber diameter is controlled between 0.5-5 microns; the fiber length formed by spinning is 5-20cm.
[0009] Furthermore, the specific process of alkaline hydrolysis in step S3 is as follows: the product obtained in step S2 is placed in an alkaline aqueous solution with a pH of 8-10, a hydrolysis temperature of 50-90°C, and a hydrolysis time of 5-12 hours. After the hydrolysis is completed, the hydrophilic gel fiber is obtained by filtration; the alkaline aqueous solution is ammonia water, sodium carbonate, or a mixture of the two.
[0010] Furthermore, the specific process of step S4 is as follows: the cross-linked mixed liquid is evenly sprayed on the surface of the hydrophilic gel fiber obtained in step S3, and after the spraying is completed, it is placed for 15-30 minutes to allow it to be fully absorbed to obtain the polyacrylic acid super hydrogel fiber cold storage material.
[0011] Furthermore, the preparation process of the cross-linked mixed liquid is as follows: ethylene glycol diglycidyl ether or propylene glycol triglycidyl ether and aziridine are dissolved in 25% to 30% methanol aqueous solution, the amount of ethylene glycol diglycidyl ether or propylene glycol triglycidyl ether is 1% to 3% of the mass of the methanol aqueous solution, and the amount of aziridine is 0.2% to 0.5% of the methanol aqueous solution; during the spraying process, the spraying amount is 6-12g per 100g of hydrogel fiber product.
[0012] The present invention also discloses a novel super hydrogel fiber cold storage material for cold chain prepared based on the preparation method, and application of the material in express delivery, cold chain and cold compress.
[0013] The invention achieves the preparation of fiber products by spinning by synthesizing acrylic hot-melt linear polymers. The polyacrylate fiber is passed through an alkaline aqueous solution to hydrolyze the polymer ester bonds to form carboxylic acid groups to achieve hydrophilic and absorption modification. The fiber surface carboxyl groups after hydrolysis are used to perform secondary stereo crosslinking with the epoxy groups of glycidyl ether to perform water-insoluble modification on the fiber surface, thereby obtaining a hydrogen-bonded crosslinked super hydrogel fiber cold storage material.
[0014] The cold storage material prepared by the present invention has a high specific heat capacity, and the material can store and release more cold, providing more effective temperature control. In terms of material structure, the material enhances its structural stability through three-dimensional cross-linking, thereby improving the cold storage performance. This structure not only provides good flexibility, but also avoids breakage during the freezing process, ensuring the recyclability and long-term stability of the cold storage material. In terms of safety, the main body of the cold storage material of the present invention is an acrylic polymer, which has good safety and can effectively ensure food safety and the health of operators during transportation. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic diagram of the preparation process of the cold storage material of the present invention. DETAILED DESCRIPTION
[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] As attached Figure 1 As shown, the present invention relates to a new type of super hydrogel fiber cold storage material for cold chain The preparation method comprises the following steps: S1, polymer synthesis, placing acrylic monomers in a solvent for polymerization to obtain a hot-melt acrylic ester polymer; The acrylic monomers include one or more combinations of acrylic acid and acrylic esters; the acrylic esters include methyl acrylate, butyl acrylate, ethyl acrylate, and propyl acrylate; the ratio of acrylic acid to acrylic ester monomers is 1:(3-5); the solvent system of the polymerization reaction is any one of cyclohexane, xylene, and ethyl acetate.
[0018] The specific process of the polymerization reaction is as follows: the acrylic acid monomer is mixed evenly with the initiator, the solvent is heated to 50-90°C in a water bath, and the monomer solution containing the initiator is slowly dripped into the reaction solvent for 1-3 hours; stirring is performed during the dripping process, and the mass of the reaction monomer is controlled to be 25%-40% of the mass of the solvent. After the monomer is dripped, the reaction temperature is maintained for 3-5 hours.
[0019] The reaction product is a granular polymer. After the heat preservation is completed, the granular product is separated from the solvent by filtration to obtain a granular product. The granular product is washed and dried to obtain a hot-melt acrylate polymer.
[0020] The initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate. The amount of the initiator is 1-5 ten-thousandths of the monomer mass.
[0021] S2, polymer hot melt spinning, the product obtained in step S1 is crushed into particles of 20 mesh or more, and formed into fiber products by hot melt high pressure spinning. The hot melt spinning temperature is 180-250 ℃, the pressure is 0.8-2.5Mpa, and the ejected filamentous fibers are cooled and solidified by normal temperature water, and the fiber diameter is controlled between 0.5-5 microns; the fiber length formed by spinning is 5-20cm.
[0022] S3, alkaline hydrolysis, subjecting the product obtained in step S2 to alkaline hydrolysis; The specific process of alkaline hydrolysis is as follows: the product obtained in step S2 is placed in an alkaline aqueous solution with a pH of 8-10, a hydrolysis temperature of 50-90° C., and a hydrolysis time of 5-12 hours. After the hydrolysis is completed, the hydrophilic gel fiber is obtained by filtration.
[0023] The alkaline aqueous solution can be ammonia water, sodium carbonate or a mixture of the two. Through the above alkaline hydrolysis process, the ester groups on the surface of the polymer are hydrolyzed to form carboxyl groups, thereby making the polymer hydrophilic and water-absorbent.
[0024] S4, three-dimensional cross-linking, using the cross-linking mixture to evenly spray the surface of the hydrophilic gel fiber obtained in step S3, and after the spraying is completed, let it stand for 15-30 minutes to allow it to fully absorb to obtain the polyacrylic acid super hydrogel fiber cold storage material.
[0025] The cross-linking mixed solution includes methanol, water, aziridine, ethylene glycol diglycidyl ether or glycerol triglycidyl ether.
[0026] The preparation process of the cross-linking mixed solution is as follows: dissolving ethylene glycol diglycidyl ether or glycerol triglycidyl ether and aziridine in a 25% to 30% methanol aqueous solution, wherein the amount of ethylene glycol diglycidyl ether or glycerol triglycidyl ether is 1% to 3% of the mass of the methanol aqueous solution, and the amount of aziridine is 0.2% to 0.5% of the methanol aqueous solution.
[0027] During the spraying process, the spraying amount is 6-12 g per 100 g of the hydrogel fiber product.
[0028] The invention achieves the preparation of fiber products by spinning by synthesizing acrylic hot-melt linear polymers. The polyacrylate fiber is passed through an alkaline aqueous solution to hydrolyze the polymer ester bonds to form carboxylic acid groups to achieve hydrophilic and absorption modification. The fiber surface carboxyl groups after hydrolysis are used to perform secondary stereo crosslinking with the epoxy groups of glycidyl ether to perform water-insoluble modification on the fiber surface, thereby obtaining a hydrogen-bonded crosslinked super hydrogel fiber cold storage material.
[0029] Based on the above preparation scheme, multiple laboratory verifications were carried out. During the preparation process, an MSK-MS-02 experimental high-pressure melt spinning machine (2800rpm / min, volume 500ml, maximum 2.5mpa, sold by Hefei Kejing) was used.
[0030] Example 1: A mixture of acrylic acid and ethyl acrylate is used in a ratio of 1:4, with a total weight of 400g. Cyclohexane is used as a solvent with a weight of 800g. It is heated to 70°C in a water bath. 12mg of azobisisobutyronitrile (3 ten-thousandths of the mass of the monomer) is mixed with the monomer and slowly added to the reaction solvent for 2 hours. After the addition is completed, the reaction temperature is maintained for 4 hours to obtain a granular polymer. After filtration, the mass of the granular polymer is about 1kg (similar to Examples 2, 3, and 4). The obtained polymer is broken into 25 mesh particles and formed into a fiber product by hot melt high-pressure spinning. The hot melt spinning temperature is set to 200°C, the pressure is 1.5Mpa, the fiber diameter is controlled to 1 micron, and the fiber length is about 10cm. Ammonia water is used to adjust the pH of the aqueous solution to 9, the hydrolysis temperature is 70°C, and the hydrolysis time is 8 hours. Then the cross-linked mixed solution is sprayed on the surface of the hydrophilic gel fiber obtained in step 3. The cross-linking mixed solution consists of methanol, water, aziridine and ethylene glycol diglycidyl ether, and the spraying amount is 8 g per 100 g of hydrogel fiber. After spraying, the mixture is left for 20 minutes.
[0031] Example 2: A mixture of acrylic acid and propyl acrylate is used in a ratio of 1:5, with a total weight of 400g. Xylene is used as a solvent with a weight of 800g. It is heated to 80°C in a water bath. 20mg of the initiator azobisisoheptanonitrile (the amount is 5 ten-thousandths of the monomer mass) is mixed with the monomer and slowly added to the reaction solvent for 2.5 hours. After the addition is completed, the reaction temperature is maintained for 3.5 hours to obtain a granular polymer. The obtained polymer is broken into particles of more than 30 meshes and formed into a fiber product by hot melt high-pressure spinning. The hot melt spinning temperature is set to 220°C, the pressure is 2Mpa, the fiber diameter is controlled at 2 microns, and the fiber length is about 15cm. Sodium carbonate is used to adjust the pH of the aqueous solution to 8, the hydrolysis temperature is 60°C, and the hydrolysis time is 6 hours. Then the cross-linked mixed solution is sprayed on the surface of the hydrophilic gel fiber obtained in step 3. The cross-linking mixed solution consists of methanol, water, aziridine and propylene glycol triglycidyl ether, and the spraying amount is 10 g per 100 g of hydrogel fiber. After spraying, the mixture is left for 25 minutes.
[0032] Example 3: A mixture of acrylic acid and methyl acrylate is used in a ratio of 1:3, with a total weight of 400g; ethyl acetate is used as a solvent, with a weight of 800g, and heated to 60°C in a water bath. After mixing the initiator dimethyl azobisisobutyrate 8mg (the amount is 2 ten-thousandths of the monomer mass) with the monomer, it is slowly added dropwise to the reaction solvent for 1.5 hours. After the addition is completed, the reaction temperature is maintained for 4.5 hours to obtain a granular polymer. The obtained polymer is broken into particles of more than 40 mesh, and a fiber product is formed by hot melt high-pressure spinning. The hot melt spinning temperature is set to 230°C, the pressure is 1.8Mpa, the fiber diameter is controlled at 3 microns, and the fiber length is about 20cm. A mixed solution of ammonia and sodium carbonate is used to adjust the pH of the aqueous solution to 9.5, the hydrolysis temperature is 80°C, and the hydrolysis time is 10 hours. Then the cross-linked mixed solution is sprayed on the surface of the hydrophilic gel fiber obtained in step 3. The cross-linking mixed solution consists of methanol, water, aziridine and ethylene glycol diglycidyl ether, and the spraying amount is 7 g per 100 g of hydrogel fiber. After spraying, the mixture is left for 15 minutes.
[0033] Example 4: A mixture of acrylic acid and butyl acrylate is used in a ratio of 1:4, with a total weight of 400g; cyclohexane is used as a solvent, with a weight of 800g, and heated to 75°C in a water bath. After mixing the initiator azobisisobutyronitrile 16mg (the amount is 4 ten-thousandths of the monomer mass) with the monomer, it is slowly added dropwise to the reaction solvent for 2.5 hours. After the addition is completed, the reaction temperature is maintained for 4 hours to obtain a granular polymer. The obtained polymer is broken into particles of more than 30 meshes, and a fiber product is formed by hot melt high-pressure spinning. The hot melt spinning temperature is set to 190°C, the pressure is 1.2Mpa, the fiber diameter is controlled at 4 microns, and the fiber length is about 10cm. Use ammonia water to adjust the pH of the aqueous solution to 8.5, the hydrolysis temperature is 70°C, and the hydrolysis time is 7 hours. Then use the cross-linked mixed solution to spray the surface of the hydrophilic gel fiber obtained in step 3. The cross-linking mixed solution consists of methanol, water, aziridine and propylene glycol triglycidyl ether, and the spraying amount is 9 g per 100 g of hydrogel fiber. After spraying, the mixture is left for 20 minutes.
[0034] The cold storage materials obtained in Examples 1, 2, 3, and 4 were tested for their specific heat capacity. The testing process was to freeze the cold storage materials at a temperature of -5 degrees Celsius, and then take a preset amount of them and heat them in an adiabatic calorimeter to measure their specific heat capacity. The specific heat capacities of Examples 1, 2, 3, and 4 were 13006 J / (kg·K), 15008 J / (kg·K), and 16006 J / (kg·K) respectively. J / (kg·K), 14005J / (kg·K), 16001J / (kg·K) are higher than the specific heat capacity of 6184J / (kg·K) of the super absorbent polymer (SAP) cold storage material used for comparison.
[0035] It should be noted that, unless otherwise clearly specified and limited, the terms such as "install", "connect", "connect", "fix", "set" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
Claims
1. A method for preparing a novel super hydrogel fiber cold storage material for cold chain, characterized in that: The steps include: S1, polymer synthesis, placing acrylic monomers in a solvent for polymerization to obtain a hot-melt acrylic ester polymer; S2, polymer hot melt spinning, crushing the product obtained in step S1 and forming a fiber product through hot melt high pressure spinning; S3, alkaline hydrolysis, subjecting the product obtained in step S2 to alkaline hydrolysis; S4, three-dimensional cross-linking, using a cross-linking mixed solution to evenly spray the surface of the hydrophilic gel fiber obtained in step S3, the cross-linking mixed solution comprising methanol, water, aziridine, ethylene glycol diglycidyl ether or glycerol triglycidyl ether.
2. The method for preparing the super hydrogel fiber cold storage material according to claim 1, characterized in that: The acrylic acid monomer in step S1 includes one or more combinations of acrylic acid and acrylic acid esters; the acrylic acid esters include methyl acrylate, butyl acrylate, ethyl acrylate, and propyl acrylate; the ratio of acrylic acid to acrylic acid ester monomers is 1:(3-5); the solvent system of the polymerization reaction is any one of cyclohexane, xylene, and ethyl acetate.
3. The method for preparing the super hydrogel fiber cold storage material according to claim 2, characterized in that: The specific process of the polymerization reaction in step S1 is as follows: the acrylic acid monomer is mixed evenly with the initiator, the solvent is heated to 50-90°C in a water bath, and the monomer solution containing the initiator is slowly dripped into the reaction solvent, and the dripping time is 1-3 hours; stirring is performed during the dripping process, and the mass of the reaction monomer is controlled to be 25%-40% of the mass of the solvent. After the monomer is dripped, the reaction temperature is maintained for 3-5 hours; after the insulation is completed, the granular product is filtered and separated from the solvent to obtain a granular product, and the granular product is washed and dried to obtain a hot-melt acrylic ester polymer; the initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate, and the amount of the initiator is 1-5 ten-thousandths of the monomer mass.
4. The method for preparing the super hydrogel fiber cold storage material according to claim 1, characterized in that: The specific process of step S2 is as follows: the product obtained in step S1 is crushed into particles larger than 20 meshes, and a fiber product is formed by hot melt high pressure spinning. The hot melt spinning temperature is 180-250°C, the pressure is 0.8-2.5Mpa, and the ejected filamentous fibers are cooled and solidified by normal temperature water, and the fiber diameter is controlled between 0.5-5 microns; the fiber length formed by spinning is 5-20cm.
5. The method for preparing the super hydrogel fiber cold storage material according to claim 1, characterized in that: The specific process of alkaline hydrolysis in step S3 is as follows: the product obtained in step S2 is placed in an alkaline aqueous solution with a pH of 8-10, a hydrolysis temperature of 50-90°C, and a hydrolysis time of 5-12 hours. After the hydrolysis is completed, the hydrophilic gel fiber is obtained by filtration; the alkaline aqueous solution is ammonia water, sodium carbonate, or a mixture of the two.
6. The method for preparing the super hydrogel fiber cold storage material according to claim 1, characterized in that: The specific process of step S4 is as follows: the cross-linking mixed liquid is evenly sprayed on the surface of the hydrophilic gel fiber obtained in step S3, and after the spraying is completed, it is placed for 15-30 minutes to allow it to be fully absorbed to obtain the polyacrylic acid super hydrogel fiber cold storage material.
7. The method for preparing the super hydrogel fiber cold storage material according to claim 6, characterized in that: The preparation process of the cross-linked mixed solution is as follows: ethylene glycol diglycidyl ether or propylene glycol triglycidyl ether and aziridine are dissolved in a 25% to 30% methanol aqueous solution, the amount of ethylene glycol diglycidyl ether or propylene glycol triglycidyl ether is 1% to 3% of the mass of the methanol aqueous solution, and the amount of aziridine is 0.2% to 0.5% of the methanol aqueous solution; during the spraying process, the spraying amount is 6-12g per 100g of hydrogel fiber product.
8. A new type of super hydrogel fiber cold storage material for cold chain prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the cold storage material according to claim 8 in express delivery, cold chain and cold compress.